Altered white matter integrity in primary restless legs syndrome patients: diffusion tensor imaging study. (August 2014) - Chang, Yongmin; Paik, Jong Soo; Lee, Hui Joong; Chang, Hyuk Won; Moon, Hye-Jin; Allen, Richard P.; Earley, Christopher J.; Cho, Yong Won
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: A prior diffusion tensor imaging (DTI) of restless legs syndrome (RLS) subjects found alterations in brain white matter (WM). The aim of this study was to explore the possible mechanism of altered integrity of brain WM in RLS patients. Methods: The DTI measurement was performed in 22 subjects with RLS and 22 age-matched control subjects. Using a voxel-based analysis, fractional anisotropy (FA) and axial and radial diffusivities (AD and RD) were compared between RLS and control subjects with a two-sample t-test, and correlation analysis was performed in RLS subjects. Results: RLS subjects demonstrated decreased FA in the genu of the corpus callosum and frontal WM adjacent to the inferior frontal gyrus compared with the control subjects. For areas of decreased FA, both the AD and RD were higher than that in the control subjects. Discussion: Our findings suggest that loss of axonal density and myelin may account for WM changes seen in a prior study of RLS subjects.